KONSEP DESAIN HOTEL RESORT BERIDENTITAS BALI DI PANTAI BUGBUG, KARANGASEM - BALI - I Gede Ramsa Wahyu Alam Sari; I Wayan Runa; Ni Wayan Meidayanti Mustika (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2020)
This tourism accommodation was built aimed at equitable development of hotels that lead to east, north and west Bali. Due to the development gap between the construction of tourism facilities which will be concentrated in South Bali, it is necessary to equalize other areas of Bali such as east, west and north Bali. It also aims to develop regional income as a domestic and foreign tourist destination. The data collection methods used are, for example, the literature study method, which is the data collection method carried out by taking the necessary data from the related literatures. Either that is done by making direct observations in the field, regarding the problem being reviewed. By jumping directly to the location and see the physical condition of the area itself. As well as documentation methods, namely taking pictures to strengthen and clarify theoretical data by taking photos directly to the object. The concept of site planning will refer to the east-west oriented spatial concept. Its implementation will form the main, intermediate and blasphemous area values. Both the concept as the rising and setting of the sun and the north south associated with mountains and the sea in zoning arrangement, the layout of the entrance or entrance, the basic form of mass, mass system, mass patterns that will produce the orientation of the mass of the building, circulation and outer space. The concept of building planning where in this concept the shape of the building of the resort hotel has almost been realized in the form of the concept of interior space or called the interior of the building that displays the dimensions of the space, material and function of the space itself, where the inner space will produce the appearance of the building or face of the facade the exterior of this resort hotel The utility system concept is not spared from buildings like humans as a container for utility buildings as a channel for the nerves of human channels or buildings so that the utility system cannot be separated from being linked to the building as for the utility system which later as a basic reference for the construction of this resort hotel or as a distribution of development tourism and increase the original income of the region especially Karangasem Regency. Keywords: Modern Tropical; Recreation; Resort Hotels